Geometry-covering based localization for Jamming attack in wireless sensor networks - SUN Yan-qiang; WANG Xiao-dong; ZHOU Xing-ming (Tongxin xuebao)
A geometry-covering based localization（GCL） algorithm was proposed with the purpose of localizing the jamming attacker in wireless sensor networks.The knowledge of the convex hull in computing geometry,especially the smallest circle covering,was utilized in the process of GCL.Simulation results showed that GCL is able to achieve higher accuracy than other comparable localization algorithms in most cases,and that has the time complexity of O（nlogn） which is proper for resource-constrained sensor networks.